PENGEMBANGAN BUKU ASESMEN SUMATIF ANAK BERKEBUTUHAN KHUSUS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS II SDN 24 BANDA ACEH - Ridhayanie; Sariakin; Siti Mayang Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Inclusive education requires assessment tools that are appropriate to the characteristics of students with special needs, particularly students with intellectual disabilities. This study aimed to develop a summative assessment book that is valid, practical, and effective in improving the learning outcomes of students with special needs in Grade II at SDN 24 Banda Aceh. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects were Grade II students with intellectual disabilities at SDN 24 Banda Aceh. Data were collected using expert validation sheets, teacher and student response questionnaires, and learning outcome tests. The results indicated that the developed summative assessment book was categorized as highly valid, highly practical, and effective in improving students’ learning outcomes. Therefore, the summative assessment book is feasible for use as an evaluation tool for students with intellectual disabilities in inclusive elementary schools. Keywords: summative assessment, students with special needs, learning outcomes